Interreligious Engagement in Urban Spaces Social, Material and Ideological Dimensions - Ipgrave, Julia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book examines interreligious dialogue from a European perspective. It features detailed case studies analysed from different disciplinary perspectives. These studies consider such activities as face-to-face discussion groups, public meetings, civic consultations with members of faith groups, and community action projects that bring together people from different faiths. Overall, the work reports on five years of qualitative empirical research gathered from different urban sites across four European cities (Hamburg, London, Stockholm, Oslo). It includes a comparative element which connects distinctive German, Scandinavian, and English experiences of the shared challenge of religious plurality. The contributors look at the issue through social, material, and ideological dimensions. They explore the following questions: Is interreligious dialogue the producer or product of social capital? What and how are different meanings produced andcontested in places of interreligious activity? What is the function of religious thinking in different forms of interreligious activity? Their answers present a detailed analysis of the variety of practices on the ground. A firm empirical foundation supports their conclusions. Readers will learn about the changing nature of urban life through increasing pluralisation and the importance of interreligious relations in the current socio-political context. They will also gain a better understanding of the conditions, processes, function, and impact of interreligious engagement in community relations, public policy, urban planning, and practical theology.
Introduction (Ipgrave, Liljestrand, and Skeie) -- Part1: Interreligious Dialogue and Social Relations -- Chapter 1. Useful Trust: Interreligious Alliances for Alevi and Bahai communities in Hamburg (Haddad) -- Chapter 2. Maintaining and Transforming Bridging Capital in Interreligious Projects: A Case Study of a Swedish Youth Project (Liljestrand) -- Chapter 3. Six Women's Interreligious Dialogue Groups in London (Ipgrave) -- Chapter 4. Interreligious Dialogue Initiatives in a Local Borough of Oslo as Experienced by Local Youth and Dialogue Activists: Prospects for the Building of Social Capital, Trust and Social Cohesion? (Lund Johannessen and Husebø) -- Part 2: Interreligious activity and the spatial dimension -- Chapter 5. The transformation of a house of prayer in Hamburg: from church to mosque (Haddad) -- Chapter 6. An historic synagogue in London's East End: the impact of interreligious activity on a traditional place of worship (Ipgrave) -- Chapter 7. A peace and reconciliation centre in the City of London: a purpose-built venue for shared worship/reflection/dialogue (Ipgrave) -- Chapter 8. 'God's House', Fisksätra: planning a dual faith worship space in metropolitan Stockholm. (Liljestrand) -- Chapter 9. A Community Garden in Hackney: transformation of neighbourhood through interreligious activity (Ipgrave) -- Chapter 10. Fryshuset Social Centre: interreligious engagement in secular spaces (Liljestrand) -- Chapter 11. The Literature House, Oslo: public space for IR dialogue (Husebø and Lund Johannessen) -- Part3: Religious thinking and Interreligious Activity -- Chapter 12. Dialogue discussion groups (Liljestrand) -- Chapter 13. Community action projects (Ipgrave) -- Chapter 14. Interreligious initiatives in schools (Husebø and Lund Johannessen) -- Chapter 15. Public platform events (Ipgrave) -- Chapter 16. Community consultation groups (Liljestrand) -- Chapter 17. Interreligious rituals (Ipgrave).
Keywords: Religion and sociology; Human geography; Sociology of Religion; Human Geography